2021
DOI: 10.1001/jamanetworkopen.2021.9041
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Treatment of Opioid Dependence With Weekly and Monthly Subcutaneous Depot vs Daily Sublingual Buprenorphine

Abstract: IMPORTANCE Patient-reported outcomes in the treatment of opioid dependence may differ between subcutaneously administered depot buprenorphine and daily sublingual buprenorphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 38 publications
4
52
0
1
Order By: Relevance
“…An open label RCT conducted in Australia [ 25 ] indicated higher treatment satisfaction, measured with the Treatment Satisfaction Questionnaire, in 60 patients receiving depot injections, compared with 59 treated with sublingual buprenorphine naloxone. Although injections site reactions were more frequent of those treated with depot injections (65%) compared to those treated with sublingual formulations (20%), no patients discontinued trial medication due to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…An open label RCT conducted in Australia [ 25 ] indicated higher treatment satisfaction, measured with the Treatment Satisfaction Questionnaire, in 60 patients receiving depot injections, compared with 59 treated with sublingual buprenorphine naloxone. Although injections site reactions were more frequent of those treated with depot injections (65%) compared to those treated with sublingual formulations (20%), no patients discontinued trial medication due to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…These long-acting buprenorphine formulations, such as the subdermal implant, as well as subcutaneous depot formulations, have the potential to reduce the risk of diversion [40]. The new depot buprenorphine formulations were found to be non-inferior to sublingual drugs, as well as more effective than a placebo, in reducing opioid use, and it is the preferred formulation vs. the sublingual one in the latest trial [41,42]. Depot buprenorphine, in custodial settings, showed treatment retention and outcomes, comparable to those observed in community settings and for other opioid agonist treatment used in custodial settings, without increased risk of diversion [43].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these formulations may provide potential advantages for correctional populations who experience challenges balancing work and other community reintegration requirements. Additionally, community-based studies and randomized control trials have found favourable attitudes towards use of extended-release OAT among patients (Ahamad et al, 2015 ; Compton & Volkow, 2021 ; Lintzeris et al, 2021 ). These realities highlight the need for the expansion of OAT options in Canada, with the goals of reducing opioid use and related health and social risks, including re-incarceration, among correctional populations with OUD following community release.…”
Section: Discussionmentioning
confidence: 99%